Is EU Membership Important for the UK’s Aerospace Industry? - Jackson, Alex (2014)
At the time of writing the UK is faced with two of the largest challenges to its international status in a generation, these issues are: The Scottish referendum in September 2014 and the current government’s scheduled referendum on European Union membership in 2017. This investigation explores the latter of these two issues. It is likely that the UK electorate in an EU referendum will be influenced by economic criteria (Portes, 2013). Studies thus far have largely focussed on the macroeconomic impacts of EU membership using econometric gravity modelling techniques and have identified difficulties in accurately modelling the impact of UK EU membership (Pain & Young, 2004, Springford & Tilford, 2013). Consequently business perceptions of EU membership are also being obtained.